Mengenal Mahatma Gandhi Dan Ajarannya - Puspo Renan Joyo (Fakultas Dharma Duta, 2019)
According to Campbell, that human life is the eternal desire of unremitting struggle for power for the sake of power and only stopped when death arrives. Hobbes assumes that the power that is the embryo of conflict. Really, history records that the human journey always coincided with the dispute, up to now, even showing increasing escalation. The middle of this dispute, Mahatma Gandhi was present as a difference that the dispute actually is not inevitable at all. Without pretending that what is delivered Gandhi is the perfect remedy to overcome war, but interestingly Gandhi gives an idea capable of dealing with so many injuries. This article explains about the profile, struggle and teachings of Gandhi.